Characterizing the Role of Glutamine synthetase Gene on Ammonia Nitrogen Detoxification Metabolism of the Razor Clam Sinonovacula constricta - Sun, Gaigai; Sun, Changsen; He, Jing; Yao, Hanhan; Dai, Wenfang; Lin, Zhihua; Dong, Yinghui (Frontiers in Marine Science, 2021)
Ammonia nitrogen is a common toxic substance in the aquatic system, which seriously threatens the survival and growth of clams. However, less is known about the ammonia metabolism and detoxification strategy in razor clam. In this study, the polymorphism of the Glutamine synthetase gene from Sinonovacula constricta (Sc-GS) was found to be related to ammonia tolerance. By comparing the coding sequence (CDS) region of Sc-GS from two geographical populations, a total of 14 and 12 single nucleotide polymorphisms (SNPs) were identified, respectively, of which 10 loci were shared between the two populations. Among them, the locus c.1133T > G exhibited an extremely significant and strong association with ammonia tolerance in both populations (P < 0.01), and it was missense mutation, which led to the amino acid change from leucine (Leu) to arginine (Arg). Furthermore, the results about H&E staining and immunohistochemistry of Sc-GS protein in gills and hepatopancreas revealed that it was specifically localized in the lateral cilia of gill filaments and the endothelial cells of hepatocytes. After inhibiting the Sc-GS expression by RNA interference (RNAi) technology, the transcript levels of Sc-GS were extremely significantly downregulated at 24, 48, 72, and 96 h (P < 0.01) in the hepatopancreas. Taken together, these results indicated that the Sc-GS gene may participate in ammonia metabolism. In addition, these results will help to demonstrate the role of Sc-GS in ammonia nitrogen metabolism and provide markers related to ammonia nitrogen tolerance for molecular marker-assisted selection (MAS) of the razor clam.